The Representation of Syrian Asylum Seekers in Turkish and Global English Media: A Van Dijkian Critical Discourse Analysis - Pınar Karaca Canpolat; Eyyüp Yaşar Kürüm (Media Antartika Indonesia, 2025)
This study examines how Syrian asylum seekers are represented in Turkish and global English-language media, with particular attention to the discursive choices through which meaning and ideology are constructed. Drawing on Van Dijk’s socio-cognitive model of Critical Discourse Analysis (CDA), the research focuses on lexical patterns, framing strategies, and structural features that shape media narratives about asylum seekers. The data set includes media content from Turkish outlets such as Hürriyet, Daily Sabah, Cumhuriyet, BirGün, and GZT, alongside global media sources including BBC, The Guardian, The New York Times, and Al Jazeera English. Covering the period between 2019 and 2025, the analysis identifies two dominant and recurring frames: humanitarian framing and securitization framing. The findings suggest that Turkish media tends to move between narratives of compassion and concerns over economic or social strain, while global media more frequently situates Türkiye within broader geopolitical and security-oriented discourses. Across both contexts, asylum seekers are largely positioned as objects of policy rather than active subjects of experience. The study argues that these representations are not neutral but reflect wider ideological struggles in which language plays a central role in shaping public perception and social cognition.